TECHNOLOGY EDUCATION IS A TECHNOLOGICAL APPROACH TO THE EDUCATIONAL PROCESS BASED ON THE PEDAGOGICAL NATURE OF ORGANIZATION - M.Kh. Ikramova; Yigitaliyeva Dildorakhan; Akhmadaliyeva Zebokhon (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes the pedagogical essence of organizing the educational process of technology education based on technological approaches. Education of the young generation requires great responsibility and knowledge from pedagogues. The methodical activity of the teacher is of great importance in the development of science.